Efektivitas Pengelolaan Alokasi Dana Desa di Desa Long Pada Kabupaten Malinau - Alvonsius Parlindungan Sinaga; Darmanto Darmanto; Pramono Sidi (Ideas Publishing, 2023)
The gradual disbursement of village funds has had a negative impact on a number of activities in Long Pada Village, but the management received can be allocated as a whole. This research method is descriptive qualitative with data coming from interviews, observation and documentation. The findings were that fund management in Long Village, Sungai Tubu District, Malinau Regency was 100% according to target. Its achievements can be said to be very effective. Based on the elements of allocation, integration and adaptation, it has been implemented well based on various implementation indicators. Supporting factors for implementation include active community participation, infrastructure, and cooperation between parties. The obstacles lie in human resources, natural conditions, and the gradual process of disbursing funds.